Pengaruh Terapi Kompres Dingin terhadap Penurunan Tingkat Nyeri pada Pasien Fraktur Tertutup Bagian Ekstremitas - Pondete, Marlyn Anggelina; Manengkey, Olvin; Palandi, Cleonira (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Fracture is a condition of broken bones, either partially or completely, due to strong physical impact or pressure. The severity of this injury is influenced by factors such as the strength and direction of the impact, the condition of the bone, and the surrounding tissue (Siam, 2023),The purpose of this study was to determine the Effect of Cold Compress Therapy on Reducing Pain Levels in Patients with Closed Fractures of the Extremities Emergency Room of Bhayangkara Hospital Class III Manado.The type of research used is quasi-experimental research research design using the pre and post test group design approach respondendt population in this study were all patients with closed fractures of the extremities who were treated at the Emergency Room of Bhayangkara Hospital as many as 21 respondents The results of the study using the Wilcoxon test showed a p Value of 0.000 0.05, so Ho was rejected and Ha was accepted, which means that there is an average difference between the pretest and post test. The conclusion of this study there is an effect of cold compress therapy on reducing pain levels in patients with closed fractures of the extremities in the Emergency Room with a p value 0.000 0.05.